A Methodology for the Identification of Topic Transitions in Interaction - Marine Riou (Discours)
Many analysts use the notion of “topic” to describe segments of discourse, whether written or spoken, and many regret that even though a considerable amount of work has been devoted to understanding and defining the notion of discourse topic, the analyst is often left without a robust methodology to apply to their own data. This paper uses a mixed-methods approach that draws on the qualitative-oriented theoretical frameworks of Conversational Analysis and Interactional Linguistics, and combines them with quantitative methods used in other sub-fields of linguistics, such as the coding schemes and inter-rater agreement measures used in Corpus Linguistics. The goal of this study is not to provide a new understanding of “topic”, but rather to propose 1) a rich definition compiled from various earlier studies and suited to the analysis of talk-in-interaction, and 2) a systematic way to apply it to new data. The ambition of the paper is to provide a methodology for a qualitative, quantitative, or mixed-methods analysis of topic-related phenomena in interaction, as one step among many in various research protocols. It provides empirical grounds for the claim that a research methodology based on the analyst’s intuitions may be a valid and robust way to identify topic transitions – if a number of precautionary steps are taken. It also proposes a practical guide to the systematic analysis of topic in interaction.